Comparative study of helical-cut notch–coil magnets for fast-field-cycling nuclear magnetic resonance - Kruber, Stephan (2014)
In this manuscript we describe an -helical-cut notch–coil magnet system designed for fast switching of the magneticfield. An attempt was made to determine the extent to which such a magnet configuration can be efficiently used for fast-field-cycling (FFC) nuclear magnetic resonance (NMR) instruments. In addition to the typical technical requirements (high field-to-power ratio, adequate electric performance for fast-switching of the magnetic field and NMR-compatible magnetic fieldhomogeneity), a tunable homogeneity within the sample volume and more uniform heat dissipation along the magnet body areincluded. A helical-cut notch–coil machined in metallic cylinders with external movable pieces was found to fit these require-ments very well. A key factor for the optimization of the magnet parameters is the use of a novel calculation procedure based ona more realistic model that consider a magnet geometry with broken azimuthal symmetry. The aim of this paper is to theoret-ically compare the proposed geometry with other existing designs. No particular prototype is presented here. A clear under-standing of the notch–coil performance was found to be an essential step for its further consideration as a potential autoadaptive(electronically controlled) magnet system for FFC applications.